PEMODELAN POTENSI PRODUKSI KUBIS (BRASSICA OLERACEA) DI KABUPATEN MALANG MENGGUNAKAN GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) DENGAN PENDEKATAN PEMBOBOTAN BI-SQUARE EKSPONENSIAL DAN GAUSSIAN - Muhammad Syahfitra; Nursamsi; Novfirman; Novi Yulanda Sari; Rio Valery Allen; Wisnu Setya Nugroho (Smart Education, 2026)
Abstract: Cabbage is one of the horticultural crops with the largest production in Indonesia. Cabbage in Malang Regency is one of the main commodities widely planted by farmers. Geographically Weighted Regression (GWR) is a statistical method used to analyze spatial influences with a point approach that shows that between locations have a tendency towards different characteristics in representing a condition. This model is applied in the agricultural sector to estimate cabbage production that varies between regions. The purpose of this study is to determine the best weighting to form a model and variables that influence cabbage production in Malang Regency, using the GWR model with fixed kernel weighting Bi-square, Exponential, and Gaussian. The best criteria are based on the coefficient of determination (R2) and the Akaike Information Criterion (AIC) statistics. Secondary data used are sourced from the Food Crops, Horticulture and Plantation Service of Malang Regency, with predictor variables including land area, elevation, and rainfall. Based on the R2 and AIC values, the analysis results indicate that the GWR model with an exponential weighting function is the best model for cabbage production, and land area is the variable that influences cabbage production in Malang Regency.Keywords: Geographically Weighted Regression, weighting function, cabbageAbstrak. Kubis menjadi salah satu tanaman hortikultura yang termasuk dalam produksi terbesar di Indonesia. Kubis di Kabupaten Malang merupakan salah satu komoditi utama yang banyak ditanam oleh petani. Geographically Weighted Regression (GWR) merupakan salah satu metode statistika yang digunakan untuk menganalisis pengaruh spasial dengan pendekatan titik yang menunjukkan bahwa antar lokasi memiliki kecenderungan terhadap karakteristik yang berbeda dalam merepresentasikan suatu kondisi. Model ini diterapkan pada bidang pertanian untuk menduga produksi kubis yang bervariasi antar daerah. Tujuan penelitian adalah untuk menentukan pembobot yang terbaik untuk membentuk model dan peubah yang berpengaruh terhadap produksi kubis di Kabupaten Malang, menggunakan model GWR dengan pembobot fixed kernel Bi-square, Eksponensial dan Gaussian. Kriteria terbaik didasarkan pada koefisien determinasi (R2) dan statistik Akaike Information Criterion (AIC). Data sekunder yang digunakan bersumber dari Dinas Tanaman Pangan Hortikultura dan Perkebunan Kabupaten Malang dengan peubah prediktor meliputi luas lahan, elevasi dan curah hujan. Berdasarkan nilai R2 dan AIC hasil analisis menunjukkan bahwa model GWR dengan fungsi pembobot eksponensial merupakan model terbaik untuk produksi kubis dan luas lahan adalah peubah yang berpengaruh terhadap produksi kubis di Kabupaten Malang.Kata Kunci : Geographically Weighted Regression, fungsi pembobot, kubis